Peramalan Hasil Produksi Ikan Kerapu Provinsi Sumatera Barat dengan Menggunakan Pemulusan Eksponensial Ganda Tipe Holt dan Triple Tipe Brown - Silvia Hanifah Derisna; Helma Helma (UNIVERSITAS NEGERI PADANG, 2022)
Grouper is marine fish found in Indonesian waters which are very popular and have high market prices. The production of grouper in West Sumatra is produced by cultivation using floating net cages and direct fishing. The purpose of this study is to form a forecasting model for grouper production of West Sumatra. Also this study to predict the production of grouper based on the model formed using Holt type double exponential smoothing and brown triple exponential smoothing. The data collection method used is data on grouper production of West Sumatra province from 2008 to 2020 which was obtained from the Marine and Fisheries Service of West Sumatra Province. The method used is Holt type double exponential smoothing and brown type triple exponential smoothing. Based on the forecasting model, the forecast results for the next 5 years have increased compared to the previous year's production. By using the Holt type double exponential smoothing method, the predicted results in the year 2021-2025 are 4553.83, 4761.96, 4970.08, 5178.20, 5383.33, while using the brown type triple exponential smoothing method the results are obtained successive forecast of 4868,89, 5160,70, 5464,24, 5779,52, 6106,53.